Francis Bacon's "inquiry touching human nature" : virtue, philosophy, and the relief of man's estate - Minkov, Svetozar, 1975- (Lexington Books, 2010)
""In this bold, beautifully written, and very personal study, Professor Svetozar Y. Minkov looks beyond the Bacon we all know---the champion of a new science, the inductive method, and the bounties of technology---to reveal a moral thinker of the first rank, whose musings on love, justice, nobility, and death both inform and ultimately eclipse his scientific project."--Tim Spiekerman, Kenyon College, author of Shakespeare's Political Realism" ""Svetozar Minkov shows us that Sir Francis Bacon, long noted for his attack on ancient natural philosophy and proposal of a new experimental and technological science of nature, was just as importantly a moral philosopher striving to understand the human condition. Minkov's book is important; it illuminates Bacon's thought and helps us think about the project of modernity."--Jerry Weinberger, Michigan State University" ""Professor Minkov gives us a string to lead us through the labyrinth of modern science and into the broader world of thought in which it is found. Students of science would well profit by understanding his thesis and would find their way out of the labyrinth, pershaps to return to it with that understanding in place."--Bernhardt L. Trout, Massachusetts Institute of Technology" ""An indispensable clarifying of modern progress. Drawing on an astonishingly wideranging selection of texts, Minkov brings out the formidable reflections on wisdom, justice, love, and other moral concerns that underlie Bacon's technological scientific project. A study itself philosophically illuminating."--Robert Faulkner, Boston College, author of Francis Bacon and the Project of Progress."